1987
DOI: 10.3109/07367228709144624
|View full text |Cite
|
Sign up to set email alerts
|

An Interpretation of Dental Innervation Based upon the Pattern of Calcitonin Gene-Related Peptide (CGRP)-Immunoreactive Thin Sensory Axons

Abstract: Calcitonin gene-related peptide (CGRP) is a recently characterized neuroactive substance that is expressed in a large proportion of small- to medium-diameter sensory ganglion neurons whose central terminals lie in the superficial spinal and medullary dorsal horn. This restricted distribution within the peripheral nervous system suggests a prominent role for the peptide in nociceptive processing. The mammalian tooth pulp, which receives a relatively homogeneous afferent input from thin (putative nociceptive) fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(76 citation statements)
references
References 78 publications
3
73
0
Order By: Relevance
“…The CGRP-containing nerve fibers distributed around blood vessels in the dental pulp are regarded as a type of nerve distinct from those involved in sensory transduction (SILVERMAN and KRUGER, 1987), although they are exclusively originated from trigeminal sensory neurons (SILVERMAN and KRUGER, 1987;WAKISAKA et al, 1987). In fact, CGRP is known to be a potent vasodilator , and acts as an enhancer of tachykinin-induced protein extravasation (BRAIN and WILLIAMS,1985;GAMSE and SARIA, 1985).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CGRP-containing nerve fibers distributed around blood vessels in the dental pulp are regarded as a type of nerve distinct from those involved in sensory transduction (SILVERMAN and KRUGER, 1987), although they are exclusively originated from trigeminal sensory neurons (SILVERMAN and KRUGER, 1987;WAKISAKA et al, 1987). In fact, CGRP is known to be a potent vasodilator , and acts as an enhancer of tachykinin-induced protein extravasation (BRAIN and WILLIAMS,1985;GAMSE and SARIA, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Recent immunohistochemical studies have revealed that nerve fibers in the dental pulp contain several neuropeptides including vasoactive intestinal polypeptide (VIP), substance P, and calcitonin gene-related peptide (CGRP) (UDDMAN et al, 1986;WAKISAKA et al, 1985;SILVERMAN and KRUGER, 1987). Among these neuropeptides, CGRP seems one of the most important because of its dense distribution in the dental pulp (HOSHINO et al, 1987;SILVERMAN and KRUGER, 1987).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some studies have showed sensory innervation in the rat incisor pulp by experimental studies involving cutting the trigeminal nerve (HIURA et al, 1973;SAKAI, 1974;KATAYAMA, 1982;KUBOTA et al, 1985), and by HRP-tracing method (FURSTMAN et al, 1975) and autoradiography (BYERS and KISH, 1976). Recently, the occurrence of sensory innervation of the rat incisor was demonstrated by immunohistochemistry for calcitonin gene-related peptides (CGRP), which are known to function as sensory neurotransmitters (SILVERMAN and KRUGER, 1987;MORI et al, 1990). MORI et al (1990) proved that these CGRP-positive nerve fibers are derived from medium to large sized neurons in the trigeminal ganglion, employing the injection of fast blue into the incisor pulp.…”
Section: LImentioning
confidence: 99%
“…t has been well known for several decades that a role in bone remodeling, on the basis of the pattern bones and the surrounding soft tissues are innervated of innervation of molar teeth (45), the strong inhibitory (31,32). Immunocytochemistry has shown that differinfluence of CGRP on osteoclastic bone resorption ent chemically defined types of fibres are involved in the innervation of the skeleton (2, 3,7,12,13,19,22,31).…”
mentioning
confidence: 99%